CHALLENGE OF ISLAMIC HIGHER EDUCATION IN INDONESIA (PTKIN) IN SOCIETY 5.0 - Mu’is, Ahmad; Huda, Achmad Miftachul (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This paper will describe The Islamic higher education of Indonesia (PTKIN) toward challenging Society 5.0 Which has been growing for several years to change identity from a specific subject, Islamic Studies like IAIN to Various Subjects and wider development management and knowledge not only study in religion but also social and science become State Islamic University (UIN). While building internal and external institutions has come the technology and global era namely revolution 4.0 and society 5.0. Those eras are based on digital, the internet of things, and artificial intelligence that used society 5.0 easier and more comfortable in life. Society era 5.0 is the answer to the 4.0 revolution that used technology and information approach for business. The global era will make a social change also not only in industry but also education. As part of the global industry, PTKIN must prepare itself to face it, many things should be prepared such as future institutional educational integration tools and the local education ecosystem; strategy, structure, technology, and culture. Society 5.0 offers an anytime and anywhere education approach, all educational operational systems digitally, AI, and IoT become a new habit to increase human knowledge for life is good to mankind. But in reality, Islamic Higher Education (IHE) isn’t already, because they must provide many components tools, structure, infrastructure, human resources, and new culture. It is challenging for IHE to prepare and adapt to this industrial revolution. By networking, sustainability commitment, human and financial investment, information and technology, innovation, a new paradigm, and good management of IHE can overcome a problem in society 5.0.